Samorząd Studentów Uniwersytetu Warszawskiego w latach 1980-1982: Monografia i dokumenty - Kunicki-Goldfinger, Marek (Księgarnia Akademicka Publishing, 2024)
THE UNIVERSITY OF WARSAW STUDENT LIAISON COMMITTEE IN THE YEARS 1980-1982 This book, which focuses on the activity of the Student Liaison Committee from September 1980 to September 1982, is divided into two parts. The first is a monographic study of the subject, while the second consists of a selection of the Committee’s documents, compiled and edited by the author of the monograph. The two parts are preceded by Professor Henryk Samsonowicz’s foreword entitled “Student Self-Governance”, in which he discusses the relationship between self-government and the traditions of Western civilisation, particularly emphasising the role of student unions in the development of universities. The first part of the book is organised into several chapters. The opening chapter explores differences between what self-government should ideally be and how much self-governance was tolerated under real socialism, from the post-Stalinist period up until 1980. The second chapter traces the grass roots efforts to establish various forms of student unionisation at Warsaw University between 1973 and 1977. Given the failure of these efforts, the chapter that follows discusses the significance of students’ illegal activities in support of self-governance, particularly as part of Student Solidarity Committees.